0062 Rotating night shift work in nurses and midwives and lifestyle. (23rd June 2014) - Peplonska, Beata; Burdelak, Weronika; Bukowska, Agnieszka; Sobala, Wojciech
Abstract : Objectives: To investigate the association between rotating night shift work and selected modifiable lifestyle factors among nurses and midwives. Method: The cross-sectional study included 725 nurses and midwives aged 40–60 (354 rotating night shift and 371 daytime workers). Occupational history and data about potential confounders were collected through in-person interview. Weight and height were measured and BMI was calculated. Associations between night shift work characteristics such as current rotating night shift work, frequency of night duties, total duration of rotating night shift work and lifestyle factors, i.e. a) smoking cigarettes, b) alcohol consumption, c) physical activity and d) BMI were examined with logistic regression and linear regression analyses adjusted for age. Results: Smoking cigarettes was associated significantly with current rotating night shift work (OR=1.4), frequency of night shifts (OR= 1.5 and OR=1.7 among women with 5–7 and ≥8 night duties/month, respectively) and longer duration of the night shift work (OR=2.1 for duration >25 yrs). The total physical activity was higher among rotating night shift nurses (242 vs. 203 MET*h/week), but OR of recreational inactivity was significantly increased among rotating night shift workers (OR=1.6). Mean BMI was significantly higher among postmenopausal women working night shifts when compared to day workers (BMI= 28.9 vs. 27.6 kg/m 2 ), with increased OR of obesity (OR=2.8). No significant associations were observed between night shift work and alcohol consumption. Conclusions: The results of our study indicate that rotating night shift work may be associated with poorer lifestyle, which may contribute to chronic diseases.